PENINGKATAN KEAMANAN STRUKTUR BANGUNAN BALAI KESEHATAN MASYARAKAT MELALUI PENGGANTIAN H-BEAM DI SEMARANG - rizky amrullah; Kuspranoto, Abdul (LPPM POLBITRADA, 2025)
A safe and sturdy building structure is an absolute requirement in supporting the operation of healthcare facilities. One of the vital structural elements is the H-BEAM type steel beam, which is the main support for the building load. At the Semarang Regional Public Health Center, damage was found to the existing H-BEAM due to corrosion and material age factors. This community service activity aims to improve the safety of the building structure through the process of removing the old H-BEAM and reinstalling a new H-BEAM that is more by standards. The implementation of the activity was carried out through several stages, starting from field surveys, damage identification, and removal of old components, to reinstallation and final testing. The results of the activity showed that the new structure provided a significant increase in the stability and durability of the building. In addition, this activity also raised awareness of the importance of regular maintenance of building structures in public facilities. This H-BEAM replacement activity not only has a technical impact but also supports the sustainability of public services in general.